From the mixed-up files of Mrs. Basil E. Frankweiler - KONIGSBURG, E.L. (New York Bantam Doubleday Dell Books for Young Readers, 1967)
From the Mixed-Up Files of Mrs. Basil E. Frankweiler by E.L. Konigsburg follows 12-year-old Claudia Kincaid and her brother Jamie as they run away from their suburban home to live in the Metropolitan Museum of Art.
English